PENGARUH KEPERCAYAAN, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN JASA OJEK ONLINE GRABBIKE - Nova Sugeng Riyadi; SRI ISFANTIN PUJI LESTARI; RETNONING AMBARWATI (STIE Wijaya Mulya, 2024)
Abstract: The purpose of this study is to determine the effect of trust, price, andpromotion on the decision to use GrabBike online motorcycle taxi services in the peopleof Surakarta city, and to determine the results whether there is a significant influence onall variables. The method in this study used 100 samples taken randomly in the people ofSurakarta city. Data collection techniques use questionnaire methods that are sharedthrough gogle forms.Based on the results of the analysis of the positive regression coefficient value of1.621 with a classification of (0.110>0.05), the hypothesis was rejected so that partialconfidence did not have a significant effect. The value of the regression coefficient ispositive value of 3.261 with a significance (0.02 >0.05) then the hypothesis is accepted sothat partially the price has a significant effect. The value of the regression coefficient ispositive value of 3.261 with a specification of (0.02>0.05) then the hypothesis is acceptedso that partially the price has a significant effect. The value of the regression coefficient ispositive 5.999 with a significance of (0.020>0.05), then the hypothesis is accepted so thatpartial promotion has a significant effect on the decision to use online motorcycle taxiservices. From the analysis of the F test is 52.899 with a significance level of 0.000, it canbe seen that the significance value in the F test is smaller than the predeterminedsignificance value of 0.05. The results in this study stated that there was a simultaneousinfluence between trust, price, and promotion on the decision to use online motorcycletaxi services in the people of Surakarta city. This analysis uses the help of the SPSS forWindows version 25 program.Keywords : Analysis Method, Trust, Price, Promotion, Usage Decision